Brand personality as a consistency factor in the pillars of CSR management in the new normal - García-Salirrosas, Elizabeth Emperatriz (2021)
ABSTRACT During such a complex crisis as the one experienced by humanity since the ﬁrst quarter of 2020, it is necessary to develop tools that contribute to creating the corporate image for organizations that are currently interested in being identiﬁed as brands with high social and environmental commitment. Likewise, elements that contribute to building strong brands during a context that has changed consumption priorities are required. For this reason, this paper aims at adapting the dimension of socially responsible brand personality (SRBP), proposed by Mayorga (2017), taking the situationexperienced dueto theCOVID-19 pandemicas anew context. The objectiveof thisresearch is to contribute to the management of corporate social responsibility (CSR) by providing, from a communicative perspective, a tool that optimizes the creation of a socially responsible image by the different stakeholders. The results allow us to conclude that there is a structural modiﬁcation of the brand personality proposed by Mayorga, which can be presumed to be generated by the current environment, and which, therefore, can be established as a pillar of CSR management in the new normal, from a relational point of view. The ﬁndings clearly identify the virtue of integrity in brand personality, which is made up of two attributes, which, in turn, are made up of 17 traits that can identify a socially responsible brand.